Developing Dewey’s Sociocultural Vision: Toward Educating Citizens in the 21st Century - Bentley, Michael L.; Fleury, Stephen C. (Critical Education, 2025)
The work of John Dewey continues to challenge educators whose work is to put theory into practice in the classroom. In the United States and elsewhere, a popular impression of Dewey and progressive education is that of inductive, child-centered pedagogy, but his writings in Democracy and Education—as well as in subsequent re-writings of previous works such as in How We Think (1910) — demonstrate that his earlier notions of inductive methods and a child-centered progressivism were supplanted by a pragmatism that was more akin to today’s social constructivism in terms of consideration of experience, subject matter, community, and the inherent tension between public and private and objective and subjective knowledge (Garrison, 1995, Prawat, 2000). Contrasting the current resurgence of a myopic psychological behaviorism ushered in by neoliberal testing and the standards movement over the past 25 years, Dewey’s turn toward recognizing the social and interactive continues to provide sustenance and hope for the development of more educationally robust schooling, both reflective and leading to a social and civil society that is more democratically infused. Here we attempt to explain how ideas Dewey first laid out in Democracy and Education have been seminal in our own pursuit and development of more philosophically vigorous contemporary constructivist theorizing whose philosophical anthropology, in contrast to most cognitively defined and confined versions, embraces and engenders a critical, creative, and emancipatory education. We will pay particular attention to the educative and emancipatory potency emanating from Dewey’s emphasis on community and communication, and exemplified in our descriptions of actual classroom practice.